Judgment in administration - Brown, Ray E. (New York : McGraw-Hill, 1966)
It is intended that the book be a very practical treatment of a very practical subject. It is concerned with the practicing judgement of the administrator. The book was written to be read by anyone who is interested in developing and improving his understanding of administration and his ability to practice it.
Includes index.
hza 10/07/2018
Loans
Keywords: Management; Public administration